2016
DOI: 10.5812/cardiovascmed.31546
|View full text |Cite
|
Sign up to set email alerts
|

Influenza H1N1 infection leading to cardiac tamponade in a previously healthy patient: A case report

Abstract: IntroductionThe cardiac manifestations of influenza A are broad, ranging from self-limited pericarditis to fatal cardiomyopathy. The 2009 H1N1 influenza A (H1N1) strain is a rare cause of pericarditis, and its role in developing a pericardial effusion leading to tamponade has infrequently been reported.Case PresentationWe describe a case of a young female with no prior cardiovascular history who presents with a pericardial effusion and shock secondary to cardiac tamponade from pericarditis due to H1N1 influenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…This individual had likely recovered from the initial viral challenge, cleared the virus, and perhaps acquired a secondary bacterial infection [9,22]. Notably, both individuals had pericardial effusions, which in humans are rare but serious sequellae of certain viral infections [46].…”
Section: Discussionmentioning
confidence: 99%
“…This individual had likely recovered from the initial viral challenge, cleared the virus, and perhaps acquired a secondary bacterial infection [9,22]. Notably, both individuals had pericardial effusions, which in humans are rare but serious sequellae of certain viral infections [46].…”
Section: Discussionmentioning
confidence: 99%
“…Ison et al also demonstrated abnormal ECG findings in 53%, 33%, 27%, and 23% of patients on days 1, 4, 11, and 28 after the onset of infections ( 16 ). In general, the cardiac manifestations of influenza virus infection - when present - become apparent at 4 to 9 days after the onset of flu symptoms ( 25 ); however, the study of Ison et al suggested that ECG abnormalities might be already present at an earlier time-point after the onset of infection. We did not attempt to obtain ECG data at an earlier time point in the present study in order to avoid the unnecessary spread of influenza infection to the medical staff; however, we should be aware of the possibility of a higher prevalence of ECG abnormalities at an earlier time point during the course of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathogenesis of pericardial effusion in the setting of myocardial viral infection is unclear, various viruses may induce pericardial effusion ( 27 ). There are few reports on influenza virus-associated pericardial effusion ( 28 , 29 ); nevertheless, it may lead to cardiac tamponade and a fatal outcome ( 25 ). The present study indicated that influenza virus-associated pericarditis may occur in approximately 2% of patients with influenza infection; thus, we should pay attention to this pathology.…”
Section: Discussionmentioning
confidence: 99%
“…However, adding such a case to the growing evidence of cardiovascular (CV) complications due to Influenza, the true incidence of myocardial and pericardial involvement could be underestimated. Cases of both myocarditis and pericardial effusion with or without tamponade physiology secondary to influenza have been reported [ 5 - 8 ] but in most cases of cardiac involvement, Influenza A was identified and not Influenza B [ 9 , 10 ] (as in our case).…”
Section: Discussionmentioning
confidence: 71%